Microgels and Nanogels at Interfaces and Emulsions: Identifying Opportunities From a Bibliometric Analysis - Fernandez-Rodriguez, Miguel Angel; Alvarez, Laura (Frontiers in Physics, 2021)
In this work, we used Bibliometrix and Biblioshiny to perform a bibliometric qualitative and quantitative analysis on the main topic "microgels and nanogels", and the sub-topic "microgels and nanogels at interfaces and emulsions". Word-counting of the titles of the publications enabled a descriptive analysis of thematic trends. A more complex conceptual analysis used the co-occurrence of words in titles, clustered into research themes with links to other themes. A thematic map allowed to characterize the centrality and density of the themes within the topic. A similar clustering of co-authorship enabled the mapping of the collaborations. We identified in this way research opportunities theme- and collaboration-wise.